Addressing Vaccination Anxiety by Nursery in Pediatric - Ahmed Mustafa Nasser Alhamoud; Ghanem Hassan Ghanem Al- Ghanem; Bassam Hassan Alghanem; Salah Habib Hussain Alsaleh; Abdulraouf Mohammed Hejji Alsheried; Murtadha Sameer Mohammed Alsulaiman; Badoor Hussain Ibrahim Alawad; Layla Habib Ibrahem Alhedaibi; Nora Saleh Taher Alharbi; Maryam Habeb Ahmed Al Muaibd; Hamidah Hussain Salman Bo Athab; Mousa Jafar Ali Albeladi; et al. (International Journal of Scientific Research and Innovative Studies, 2022)
Vaccination anxiety is a significant concern among parents, leading to vaccine hesitancy and low vaccination rates in pediatric populations. This review explores the role of nursery staff in addressing vaccination anxiety among parents and caregivers. By providing education, support, and reassurance, nursery staff can play a vital role in promoting vaccination acceptance and improving vaccination rates in pediatric populations.